SIMULASI MODEL ALOKASI KEBUTUHAN RUANG KOTA/ WILAYAH BERDASARKAN KEBERLANJUTAN FUNGSI KONSERVASI AIR DAN PENCEGAH BANJIR - Nawa Suwedi (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2006)
Regional Spatial Planning (RTRW) of a city or a region becomesimportant due to limitation of land, while land necessity is increasing. Inorder to achive the sustainable city / region, the attention to naturalcapabilities on water conservation and flood protection should be adaptedon RTRW. The RTRW should prevent the exsisting capabilities andincrease when the capabilitis are less. Using simulation of model as tool of analysis in the spatial planningprocess, we can see the city/ region capabilities on water conservation andflood protection, and then make decision on spatial use of the city / region.The simulation in this study was applied in the City of Batam, which wasfocused in Batam Island by using data on the year of 2000. The results ofthe simulation shows that regions which are categorized as having high andvery high capabilities on water conservation occupied only 13,36%, whilethose that have high and very high capabilities on flood protection is about23,75% of the island area. By applying of reboisation scenarios, theregions that have high and very high capabilities on water conservation canbe increased to become 56,97% and those that have high and very highcapabilities on flood protection increase to 53.58% of the island area.